Gambaran Kualitas Tidur Penjaga Malam di Universitas Jenderal Soedirman - Yusri Zahirah; Made Sumarwati; Galih Noor Alivian (Journal of Bionursing, 2021)
Background : The night watchman has the duty and responsibility of carrying out his duties at night for the security of the surroundings. These activities affect sleep and rest time so that it can have an impact on the emergence of disturbances due to inadequate sleep quality, so efforts are needed to improve sleep quality so that sleep quality is good. Research aim : This research aimed to describe the quality of sleep and efforts to improve the sleep quality on nicht watchman at Jenderal Soedirman University. Research method : This type of research is a non-experimental quantitative research. The technique used was stratified random sampling with a sample size of 58 people. The research instrument used the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the questionnaire to improve sleep quality. Univariate analysis data. Research result : The results showed that the average respondents were 37 years old, the average working period of the respondents was 10 years, the majority of the respondents' last education was at high school as many as 49 people (84.5%). Most of the respondents had poor sleep quality (89.7%) and most of the night watchman at Jenderal Soedirman University had efforts to improve the quality of sleep, namely (62.1%). Conclusion : The results of this study can be concluded that most of the night watchman have poor sleep quality, so it is necessary to manage sleep time and improve efforts to improve sleep quality.